Comparison of Treatment Outcome of the Effectiveness of Isometric Exercises as Compared to General Exercises with Cervical Spine Mobilization in The Management of Chronic Non Specific Neck Pain (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of this study was to evaluate the “effectiveness of isometric exercises as compared to general exercises along with cervical spinal mobilization to reduce pain, disability and to increase range of motion in chronic non-specific neck pain”For this randomized controlled experiment total 32 patients (16 in each group) with chronic non-specific neck pain were recruited from physiotherapy Ward Mayo Hospital Lahore, Department of Physiotherapy King Edward Medical University Lahore between October, 2019 and March, 2020. Simple randomization method was used to assign participants into isometric exercise group and general exercise with cervical spine mobilization group. The isometric exercise group performed exercises for neck muscle groups with a rubber band and general exercises with cervical mobilization group performed active range of movement exercises for all neck movements. Patients in both groups received 4 supervised treatment sessions per week for 6 weeks. Visual Analogue Scale (VAS), Neck disability index Questionnaire and goniometer were used to assess pain, disability and neck range of movements at baseline and after 6 weeks.Both interventions showed statistically significant improvements in pain, function and range of movement p = 0.001for isometric exercise group, p = 0.05 for general exercises group and p=